Scandium Triflate Catalyzed Nazarov Cyclization of Arylvinyl Epoxides Derived from Alkoxides and Chloro(aryl)carbenes: A Facile Access to Resveratrol-Derived Natural Products - Satish, Nagam; Sudhakar, Gangarajula (Synlett, 2020)
The reaction of arylvinyl alkoxides with chloro(aryl)carbenes provided the corresponding arylvinyl epoxides that underwent Nazarov cyclization in a catalytic amount of scandium triflate, providing easy access to several highly substituted indenes, including some resveratrol-derived natural products.
Keywords: Nazarov cyclization; arylvinyl alcohol; arylvinyl epoxides; indenes; resveratrol-derived natural products; scandium triflate; chloro(aryl)carbenes